Strategi Perpustakaan Untuk Memperoleh Akreditasi Perpustakaan Di SMP Negeri 1 Pekanbaru - Dyone, Fahira; Triono Dul Hakim; Rismayeti Rismayeti (Lembaga Pengembangan Kinerja Dosen, 2023)
This study aims to determine the library strategy to obtain library accreditation at SMP Negeri 1 Pekanbaru. This study uses a qualitative approach with a descriptive research design with the main objective of providing an objective description or description of a situation. The method used is observation, interviews, documentation. The results of this study found that the strategies carried out by the head of the library Insan Cendikia to obtain national school library accreditation were procurement of books, procurement of infrastructure, arrangement of equipment in the library, cataloging and human resource development. The supporting factor is the existence of a library card number (NPP), the library building has reached an area of ​​168m² and there is a reading area, work area and bookshelf area and the books are neatly arranged, there is a library management structure, the relationship between the librarian and the head of the library is quite good , the number of collections of library materials has met the national school library standards as many as 2,520 titles with 2,737 copies and professional human resources, while the inhibiting factors are insufficient funding, incomplete facilities and infrastructure, insufficient book procurement, and support from school principals who less strong.